(untitled) (Indian Journal of Animal Production and Management, 2013)
A survey was conducted to study the wool shearing practices of Deccani sheep followed by sheep farmers under filed condition and GFY in Telangana region of Andhra Pradesh. Majority (55.59%) of the sheep farmers shorn sheep twice (83.71 %) in a year manually by hired labour. Most (95.53%) of the farmers felt that no market was available for wool in the study area. Zone had significant (P<0.01) influence on GFY. The GFY was significantly (P<0.01) higher in male (362.54 ± 2.95 g) compared to female (322.29 ± 2.12 g) in the study area. Two-toothed animals had the highest wool production (388.72 ± 3.22g) in the study area compared to other ages.